증강현실 콘텐츠 기반 수업이 학업성취, 학습흥미, 몰입에 미치는 효과 - 노경희(Kyung-Hee Noh); 지형근(Hyung-Keun Jee); 임석현(Sukhyun Lim) (한국콘텐츠학회 논문지, 10(2), 2010)
The purpose of this experimental study is to find out the effect of augmented reality contents based instruction on academic achievement, interest and flow of learning. The subjects were 142 students of five classes, sampled from 6th graders of an elementary school. Three classes(86 students) were taught by augmented reality based instruction and the other two classes(56 students) were taught by textbook based instruction for 2 weeks. The experimental design of the study was the pretest-posttest control group design. The results are summarized as follows: First, there is a significant difference in academic achievement between two groups. Augmented reality based instruction group accomplished higher achievement than textbook based instruction group. Second, there is no significant difference in general interest of learning between two groups. But in the interest of lessons taken by students themselves, augmented reality based instruction is more effective than textbook based instruction. Finally, there is a significant difference in learning flow between two groups. Augmented reality based instruction group showed higher learning flow than textbook based instruction group. 본 연구는 증강현실 콘텐츠 기반 수업이 학업성취, 학습흥미, 몰입에 미치는 효과를 알아보기 위해 수행되었다. 연구대상은 초등학교 6학년 5개 반 142명을 선정하였으며, 이중 3개 학급(86명)은 증강현실 수업을, 2개 학급(56명)은 교과서 중심의 일반 수업을 각각 2주간 처치하였다. 본 연구를 통하여 얻은 결과는 첫째, 학업성취에 있어서 증강현실 수업은 교과서 중심수업보다 더 효과적이었다. 둘째, 일반적 학습흥미에 있어서는 두 집단 간 유의한 차이가 없었으나, 수업자체에 대한 흥미에 있어서는 증강현실 수업 집단이보다 높은 흥미를 나타냈다. 셋째, 학습몰입에 있어서 증강현실 수업 집단은 교과서 중심 수업 집단보다 더 높은 수준의 몰입을 보였다. 본 연구가 실제 교실상황에서 정규교육과정의 일환으로 수행되었다는 점을 고려해 볼 때, 이러한 연구결과는 증강현실 콘텐츠 기반 수업이 기존의 교과서 중심 수업과 같은 전통적 수업을 보완할 수 있는 대안적 수업방법임을 시사한다.